2018
DOI: 10.1016/j.compag.2018.09.037
|View full text |Cite
|
Sign up to set email alerts
|

A decision support tool to enhance agricultural growth in the Mékrou river basin (West Africa)

Abstract: HighlightsAn effective DSS integrating several models and methods has been developed.The E-water tool enable the identification of site-specific agronomic practices for nutrients and water management.Identified optimal solutions take into account food demand thus coping with food security issue.The main features of the DSS are tested by applying it to various scenarios in the Mékrou river basin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In the nodes of this group, contributions to sustainable management in agricultural processes were distinguished to improve the state of the soil and practices for the care and development of plantations, identify the main actors, and increase community awareness. Support models for decision making are one of the main components needed to handle and analyze a heterogeneity of data and problems related to the variance of resources, commercialization, and production trends [71,[80][81][82]. However, no contributions were identified that indicate learning or mechanisms for the relationship management and intervention of different actors.…”
Section: Management 11mentioning
confidence: 99%
See 1 more Smart Citation
“…In the nodes of this group, contributions to sustainable management in agricultural processes were distinguished to improve the state of the soil and practices for the care and development of plantations, identify the main actors, and increase community awareness. Support models for decision making are one of the main components needed to handle and analyze a heterogeneity of data and problems related to the variance of resources, commercialization, and production trends [71,[80][81][82]. However, no contributions were identified that indicate learning or mechanisms for the relationship management and intervention of different actors.…”
Section: Management 11mentioning
confidence: 99%
“…making are one of the main components needed to handle and analyze a heterogeneity of data and problems related to the variance of resources, commercialization, and production trends [71,[80][81][82]. However, no contributions were identified that indicate learning or mechanisms for the relationship management and intervention of different actors.…”
Section: Governance and Policy 67mentioning
confidence: 99%
“…In [22], the authors predicted pest population dynamics using time series clustering and structural change detection of different pest species and groups. In [24], the authors provide optimal management solutions to efficiently identify nutrients and water; a multi-objective genetic algorithm was used to implement an E-Water system. Finally, in [19], [20] and [21] the authors presented interesting decision support systems for early warning, soil nutrient and financial services, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…DSSs are currently gaining widespread use and practical application in many diverse fields of activity (where it is necessary to analyse alternative options, compare them and make an optimal choice) in solving problems of assessing the quality of organizational, design, engineering and managerial decisions (Uzdenova, 2010; Keenan and Jankowski, 2019), for example in telecommunications, banking, insurance, retail, medicine, industry, applied chemistry, molecular genetics and genetic engineering. In this aspect, agriculture is no exception (Borozenets and Tsysar, 2013; Udias et al, 2018). Thus, information and communication technologies have found application, in particular, in the field of agriculture (Chimonyo et al 2016; Graetskaya et al 2018), ecology (Pulsani, 2017; Anandhi et al 2018; Kazak and Świaçder, 2018), forestry management (Khanina et al 2009; Sakellariou et al, 2017; Kašpar et al, 2018; Kazak et al 2018) and water resources (Pulido‐Velazquez et al, 2016; Cavazza et al, 2018; Neilsen et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%